2015
DOI: 10.1021/ml5005014
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Series of Thienopyrimidine as Highly Potent and Selective PI3K Inhibitors

Abstract: Inhibition of the phosphoinositide 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signaling pathway provides a promising new approach for cancer therapy. Through a rational design, a novel series of thienopyrimidine was discovered as highly potent and selective PI3K inhibitors. These thienopyrimidine derivatives were demonstrated to bear nanomolar PI3Kα inhibitory potency with over 100-fold selectivity against mTOR kinase. The lead compounds 6g and 6k showed good developability profiles in cell-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 17 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…Substituted ethyl 2-aminothiophene -3-carboxylate(I) has been used in numerous reactions to attain the desired scaffold(A) through different routes. Han et al [13]reported the reaction of (I)with formamidine acetate in N methylpyrrolidone at 135°C under argon affording the scaffold (A)(route a).Rashmiet al [14] reportedrefluxing compound (I) with formamide (route b) to afford (A).Youla S. et al [15]accomplished the synthesis of the final compound (A) by refluxingsubstituted 5-amino-4-cyanothiophenederivatives (II) with formic acid in presence of sulphuric acid (route c).…”
Section: Synthetic Strategymentioning
confidence: 99%
“…Substituted ethyl 2-aminothiophene -3-carboxylate(I) has been used in numerous reactions to attain the desired scaffold(A) through different routes. Han et al [13]reported the reaction of (I)with formamidine acetate in N methylpyrrolidone at 135°C under argon affording the scaffold (A)(route a).Rashmiet al [14] reportedrefluxing compound (I) with formamide (route b) to afford (A).Youla S. et al [15]accomplished the synthesis of the final compound (A) by refluxingsubstituted 5-amino-4-cyanothiophenederivatives (II) with formic acid in presence of sulphuric acid (route c).…”
Section: Synthetic Strategymentioning
confidence: 99%
“…Four of the thienopyrimidine analogues (5a-5d) exhibited good inhibitory activity against FLT3 (IC 50 range from 0.055 to 0.208 lM) with similar or improved activities compared to AC220, a selective FLT3 inhibitor (IC 50 = 0.120 lM). In addition to the kinase Paper Discovery of a novel series of thienopyrimidine as highly potent and selective PI3K inhibitors (Han et al 2015) mTOR/PI3Ka Paper Design, synthesis and docking studies of novel thienopyrimidine derivatives bearing chromone moiety as mTORa/ PI3Ka inhibitors (Zhu et al 2015) EGFR Paper Truncated structures used in search for new lead compounds and in a retrospective analysis of thienopyrimidine-abased EGFR inhibitors (Bugge et al 2015) Aurora A Paper Identification of new novel scaffold for Aurora A inhibition by pharmacophore modeling and virtual screening (Chavan et al 2014) Aurora B Paper A thienopyrimidine derivative induces growth inhibition and apoptosis in human cancer cell lines via inhibiting aurora B kinase activity (Li et al 2013) ErbB2…”
Section: Resultsmentioning
confidence: 99%
“…Two compounds 20a , c were selected for further profiling, they showed single to low double digit nanomolar potencies against different PI3Kβ, PI3Kδ, and PI3Kγ enabling satisfactory developability profiles in cell‐based proliferation and ADME assays (Table ) .…”
Section: Tyrosine Kinasesmentioning
confidence: 99%
“…Using stick representation where carbon atoms are magenta colored, the hydrogen bonds are shown in yellow dashed lines to the hinge region (Val882), Lys833, and the conserved water molecule in the selectivity pocket. The interaction between the sulfur in the thienopyrimidine core of 20a and carbonyl of Glu880 is showed in magenta dashed line .…”
Section: Tyrosine Kinasesmentioning
confidence: 99%
See 1 more Smart Citation